Tibetan peach pie ebook A true account of an imaginative life. - Robbins, Tom (2024)
Internationally bestselling novelist and American icon Tom Robbins' legendary memoir—wild tales of his life and times, both at home and around the globe. Tom Robbins' warm, wise, and wonderfully weird novels—including Still Life with Woodpecker, Jitterbug Perfume, and Fierce Invalids Home from Hot Climates—provide an entryway into the frontier of his singular imagination. Madcap but sincere, pulsating with strong social and philosophical undercurrents, his irreverent classics have introduced countless readers to natural born hitchhiking cowgirls, born-again monkeys, a philosophizing can of beans, exiled royalty, and problematic redheads. In Tibetan Peach Pie, Robbins turns that unparalleled literary sensibility inward, stitching together stories of his unconventional life, from his Appalachian childhood to his globetrotting adventures —told in his unique voice that combines the sweet and sly, the spiritual and earthy. The grandchild of Baptist preachers, Robbins would become over the course of half a century a poet-interruptus, an air force weatherman, a radio DJ, an art-critic-turned-psychedelic-journeyman, a world-famous novelist, and a counter-culture hero, leading a life as unlikely, magical, and bizarre as those of his quixotic characters. Robbins offers intimate snapshots of Appalachia during the Great Depression, the West Coast during the Sixties psychedelic revolution, international roving before homeland security monitored our travels, and New York publishing when it still relied on trees. Written with the big-hearted comedy and mesmerizing linguistic invention for which he is known, Tibetan Peach Pie is an invitation into the private world of a literary legend. "A rollicking reminiscence of his Appalachian upbringing, his spiral through the psychedelic '60s, and his unconventional path to literary stardom." — O, The Oprah Magazine